Experiencing Smart Tourism Destinations in Madrid: primary and secondary drivers - San Martín Romero, Aitor; de Esteban Curiel, Javier; Antonovica, Arta (RITUR - Revista Iberoamericana de Turismo, 2019)
This paper takes into account a new paradigm for destination management based on the concept of “Smart Tourism Destination” (STD). Indeed, managing destinations is a crucial part of controlling the economic, social and environmental impacts of tourism-related activities. In this sense, a deeper approach for STD is proposed in this research, based on the management of four pillars (i.e. technology, innovation, accessibility and sustainability) to achieve efficiency and enable guests enjoy enhanced comfort and convenience. In this context, STDs seem to rise in popularity for being the trend of the future by local authorities, service companies and travelers. Thus, STDs are analyzed from the scope of some experts and Madrid visitor’s perspective for showing their benefits and drawbacks by implementing this tourism model. In particular, two protocol interviews with experts and a face-to-face survey were conducted in Madrid in order to investigate the main causes and effects of STDs. The findings of the papers state that technology is a driver to enhance the experience of visiting Madrid as STD and this technology increases the environmental awareness of visitors. These findings have been treated with content analysis and statistical procedures based on univariate, bivariate and multivariate techniques.